Mosquitoes (Diptera: Culicidae) in the Dark—Highlighting the Importance of Genetically Identifying Mosquito Populations in Subterranean Environments of Central Europe - Carina Zittra; Simon Vitecek; Joana Teixeira; Dieter Weber; Bernadette Schindelegger; Francis Schaffner; Alexander M. Weigand (Pathogens, 2021)
The common house mosquito, Culex pipiens s. l. is part of the morphologically hardly or non-distinguishable Culex pipiens complex. Upcoming molecular methods allowed us to identify members of mosquito populations that are characterized by differences in behavior, physiology, host and habitat preferences and thereof resulting in varying pathogen load and vector potential to deal with. In the last years, urban and surrounding periurban areas were of special interest due to the higher transmission risk of pathogens of medical and veterinary importance. Recently, surveys of underground habitats were performed to fully evaluate the spatial distribution of rare members of the Cx. pipiens complex in Europe. Subterranean environments and their contribution to mosquito-borne pathogen transmission are virtually unknown. Herein, we review the underground community structures of this species complex in Europe, add new data to Germany and provide the first reports of the Cx. pipiens complex and usually rarely found mosquito taxa in underground areas of Luxembourg. Furthermore, we report the first finding of Culiseta glaphyroptera in Luxembourg. Our results highlight the need for molecular specimen identifications to correctly and most comprehensively characterize subterranean mosquito community structures.